Rekayasa Lalu Lintas Ruas Jalan Di Sekitar Terminal Kepuhsari Kabupaten Jombang Guna Meningkatkan Pendapatan Asli Daerah dari Sektor Retribusi Angkutan Umum - Cahyono, Iwan; Arfaah, Saiful (Politeknik Negeri Ujung Pandang, 2017)
Traffic engineering that has been designed around this Kepuhsari terminal is to apply turn right at the intersection Jl.Brawijaya-Jl.Soekarno Hatta-Jl. Mastrip Jombang for public transportation or bus from Surabaya. Then through Jl. Mastrip to stop or enter at Kepuhsari terminal. Segment Jl. Jombang Mastrip is a type 2/1 UD (Undivided) road which is used as bus exit or public transportation access from terminal to out of town Jombang. Then this road segment is changed to type 2/2 undivided. Performance analysis at peak hour on Jl. Mastrip Jombang after the change of the type to 2/2 UD using the method of Manual Capacity of Road Indonesia (MKJI) 1997. Retrieved capacity segment Jl. Mastrip (2/2UD) = 2552 smp/days, and the value of volume and capacity ratio (v/c ratio) is 0.54 means that the current condition of the traffic in the Jl. Mastrip is still stable. While in the next 5 years, the value of volume and capacity ratio (v/c ratio) is 0.72, that the condition of traffic flow is relatively stable. But the volume and capacity ratio is in critical condition (terms of v/c ratio is â‰¤0,75). Because many buses do not enter the Kepuhsari Terminal, the Government of Jombang suffers a loss of Rp. 82 million per year. With the design of traffic engineering on roads around Kepuhsari Terminal, it can increase the regional finance from of the entrance tax for public transport or buses entering the terminal by 33.7%.